2011
DOI: 10.3390/ijms12085011
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Structure Requirement for 5-HT6 Binding Affinity of Arylsulfonyl Derivatives: A Computational Study

Abstract: 5-HT6 receptor has been implicated in a series of diseases including anxiety, depression, schizophrenia and cognitive dysfunctions. 5-HT6 ligands have been reported to play a significant role in the treatment for central nervous system (CNS) diseases. Presently, a large series of 223 5-HT6 ligands were studied using a combinational method by 3D-QSAR, molecular docking and molecular dynamics calculations for further improvement of potency. The optimal 3D models exhibit satisfying statistical results with r2ncv,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…Another descriptor whose value must be lowered due to its negative coefficient in Model-1 to have a better pKi value is sp3N_sp2O_8B. It counts the total number of sp 3 hybridized nitrogen atoms present within eight bonds of sp 2 -hybridized oxygen atoms. Of the 383 molecules with Ki ≤ 10 nM, 181 molecules lack such a combination of nitrogen and oxygen atoms, whereas the remaining 201 molecules possess only one such combination.…”
Section: Discussionmentioning
confidence: 99%
“…Another descriptor whose value must be lowered due to its negative coefficient in Model-1 to have a better pKi value is sp3N_sp2O_8B. It counts the total number of sp 3 hybridized nitrogen atoms present within eight bonds of sp 2 -hybridized oxygen atoms. Of the 383 molecules with Ki ≤ 10 nM, 181 molecules lack such a combination of nitrogen and oxygen atoms, whereas the remaining 201 molecules possess only one such combination.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach was investigated by Yahiaoui et al, who reported the design of the dual compound 27 with 5-HT4R agonist and 5-HT6R antagonist effects (Figure 8) [55]. The dual 5-HT4R/5-HT6R ligand was designed through modulation of the 5-HT4R partial agonist, RS67333 (19) by introducing a 5-HT6R antagonist (28,29) pharmacophore (a positive ionizable atom, a hydrogen bond acceptor group, a hydrophobic site, and an aromatic-ring hydrophobic site) [56][57][58][59][60]. Yahiaoui et al synthesized and tested a library of structures consisting of RS67333 ( 19) modulated with various arylsulfonyl groups (sulfonamides and sulfones) attached to the piperidine moiety through a variable number of methylene groups [61].…”
Section: Figurementioning
confidence: 99%
“…19 The most accurate homology model of the 5-Ht 6 R was downloaded from the Protein Data Bank (PDB-ID: 2RH1). 9 In this context, Fig. 3 shows the molecular couplings (after a blind docking study) between the modeled compounds 9A-I with the 5-Ht 6 R model surface.…”
mentioning
confidence: 99%
“…These latter bioactive compounds exhibited values of pK i (M) = 7.48 and 6.30, respectively. 9 All reported methods to synthesize compounds containing the azepino [4,5-b]indol-4-one framework involve the use of precursors prepared stepwise (4-8). The key step towards synthesizing this heterocyclic system is the construction of the sevenmembered ring via (i) S E Ar, 10 (ii) lactamizations, 11 (iii) Pdcatalyzed alkyne arylations, 12 (iv) photocyclizations, 13 or (v) free radical cyclizations 14 (Scheme 1).…”
mentioning
confidence: 99%